Piezoresistive silicon thin film sensor array for biomedical applications - Alpuim, P. (2011)
N-type hydrogenated nanocrystalline silicon thin film piezoresistors, with gauge factor −28, were deposited on rugged and flexible polyimide foils by Hot-wire chemical vapor deposition using a tantalum filament heated to 1750 °C. The piezoresistive response under cyclic quasi-static and dynamical (up to 100 Hz) load conditions is reported. Test structures, consisting of microresistors having lateral dimensions in the range from 50 to 100 μm and thickness of 120 nm were defined in an array by reactive ion etching. Metallic pads, forming ohmic contacts to the sensing elements, were defined by a lift-off process. A readout circuit for the array consisting in a mutiplexer on each row and column of the matrix is proposed. The digital data will be processed, interpreted and stored internally by an ultra low-power micro controller, also responsible for the communication of two-way wireless data, e.g. from inside to outside the human body.© 2011 Elsevier B.V. All rights reserved